Civil Responsibility in the Medical Industry for Artificial Intelligence Applications: the Legal Rules of AI Responsibility - Ammar Kareim Kadham Al-Bsherawy; Ali Abdul-Jabbar Rahim Al-Mashhadi (Institute of Medico-legal Publications Pvt Ltd, 2021)
The paper addresses the debate on AI robots’ legal status, which often confuses the jurisprudence and decision-makers between these synthetic drugs’ legal effect and the legal personality status. If only the theories of jurisprudence or philosophers’ opinions contribute to the law’s development, engineers with their inventions also contribute to its effect. It considers the trends in this field and the actions made by specialists in artificial intelligence, and the independence of robots based on the latter. The lack of systems of responsibility traditional to absorb the damage caused by AI technologies. The European civil law commission for robotics is awarded the most sophisticated and independent robot’s legal personality for holding them responsible for themselves and not human beings. Still, this proposal faces many legal, moral, and philosophical challenges. According to this framework, the paper aims to shed more light on, discuss and analyze such an intelligent position robot might have from legal, ethical, and philosophical aspects. The article also explores the possibility of granting autonomous robots a new legal status that removes them from the circle of things and places them within the scope of personal. What is the point of giving this legal personality to robots based on artificial intelligence advocated by international institutions and researchers in law? The results show that granting legal personality within intelligent robots’ philosophical concept is possible as it exists. However, robots’ moral nature differs from a legal person’s existence because we see and feel the latter